Educational research : an introduction - Borg, Walter R.; Gall, Meredith D. (New York : Longman, 1983)
Educational Research, 6/e, provides the most comprehensive introduction to the major research methods and types of data analysis used in educational inquiry today. Sixth Edition includes extensive coverage of qualitative inquiry.
Includes bibliographies and indexes.
Keywords: Education -- Research -- United States; Research